Changing Scenario of Language Classrooms in the Present Day World (Journal of NELTA, 2018)
The success or failure of language learning and teaching primarily depends upon the activities largely done by teachers and students in classrooms. Moreover, modern educational experts and scholars indicate the need for creating new kind of classroom scenario considering the various factors that differ from one context to another or from one classroom to another. The difference can be in the field of linguistic and cultural background of the students, their needs and interests, and other explicit or implicit areas. This article highlights eight different factors that contribute to creating successful and enjoyable language learning environment addressing the demand of changing scenario of language classrooms in the present day world. Finally, the article justifies the need for new kind of language classrooms providing some crucial evidences. Journal of NELTA, Vol 20 No. 1-2, December 2015, Page:63-70